ESG Performance and Portfolio Selection: The Case of the French Market - Belkhir, Nadia; Belhadj, Hana; BenHamad, Salah (Journal of Posthumanism, 2025)
This article analyzes the effect of environmental, social, and governance (ESG) criteria on the choice and performance of financial portfolios. The study focuses on a sample of nine French industrial companies from the CAC 40, over the period from October 2016 to December 2022, divided into two sub-periods (before and during the crisis) using the k-means method. Three portfolios were constructed using genetic algorithms, according to the companies' ESG score level (high, medium, low), then compared using the stochastic dominance approach. The results show that before the crisis, portfolios with a high ESG score dominate others according to second- and third order. However, this dominance disappears during the crisis, highlighting the sensitivity of ESG performance to market conditions.